Previous Leisure-Time Physical Activity Dose Dependently Decreases Ischemic Stroke Severity - Dominique Deplanque; Isabelle Masse; Christian Libersa; Didier Leys; Régis Bordet (Stroke Research and Treatment)
In the present subanalysis of a cross-sectional study showing the favorable effect of prior transient ischemia, leisure-time physical activity, and lipid-lowering drug therapy on stroke severity, we aimed to evaluate whether previous physical activity was dose dependently associated to minor stroke (NIHSS 0–3) and to identify possible underlying factors. Among 362 consecutive patients, less severe stroke was related to weekly exercise duration prior to stroke (no exercise: 36.1%; <2 hours: 49.3%; 2–5 hours: 58.8%; >5 hours: 64.0%; 𝑃=0.003). Only weak and moderate exercise practices were protective (weak: 50.0%; moderate: 79.3%; heavy: 22.2%; 𝑃<0.0001). Such a beneficial effect was observed independently of age and was associated with a trend to a lower frequency of arterial hypertension, alcohol abuse, and a better metabolic profile. Besides other therapeutic approaches, physical activity may be a simple way to decrease cerebral ischemia severity.